Notes techniques - collaborateurs, Divers (Assurances, 1982)
Mr. Michel Beaudoin, eng., expounds upon two new types of automatic sprinkler systems: the first one is commonly referred to as large drop system and is suited for certain industrial or commercial buildings. The second is intended for use in homes. In this respect, Mr. Louis-Paul Béguin of l’Office de la langue française presents a brief study of automatic sprinkler system including a vocabulary the which is complemented by terminological excerpts compiled long ago by Mr. Gérard Parizeau and updated by Mr. Beaudoin.